Stakeholder Perspectives on School-Based Guidance and Counseling in Uganda: Emerging Priorities for Student Support and Teacher Training - Knettel, Brandon A.; Luke, Melissa M.; Kiweewa, John M.; Nsubuga, Henry; Darkis, Jessie T.; Afriyie, Obi; Ojiambo, Deborah (International Journal for the Advancement of Counselling, 2020)
School guidance and counseling services in Uganda are limited, but are gradually gaining traction despite resource constraints. We conducted qualitative interviews with 22 counselors, school administrators, and government officials involved in secondary school counseling in the Kampala district to assess future needs. Interview data focused on three central domains: existing guidance and counseling efforts, barriers to providing effective services, and the future outlook of the profession. As school counseling gains support, counselors require new resources and training to support effective and sustainable practice. Future efforts must appeal to school and government leaders with a return on investment demonstrated through academic and broader student success.
Keywords: Consensual qualitative research; Comprehensive guidance and counseling programs; East Africa; Uganda; School counseling; Teacher training